Kualitas Papan Partikel Kayu Limbah Gergajian Meranti Putih dan Purun Danau Menggunakan Perekat Poliuretan: The Quality of Particleboards from White from Waste Wood Meranti and Purun Danau Sawdust Using Polyurethane Adhesive - Indrayanti, Lies; Santoso, Mahdi; Yanarita, Yanarita; Saragih, Jon Riston (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
This study aims to evaluate the quality of particleboard made from a combination of white meranti wood particles and purun. The research is conducted at the Laboratory of Forest Products Technology and Forest Management, Department of Forestry, Faculty of Agriculture, Universitas Palangka Raya. A Complete Randomized Design with a single factor—particle composition ratio of white meranti to purun (100:0, 75:25, 50:50, 0:100)—is applied. The result shows that moisture content, density, thickness swelling, internal bonding, and screw withdrawal strength met the requirements of SNI 03-2105-2006. However, the Modulus of Elasticity (MOE) and Modulus of Rupture (MOR) values do meet the standard, indicating that the composition variation do not improve these parameters. ANOVA reveals that particle composition has no significant effect on all parameters except water absorption and internal bonding. Duncan’s test indicates that the 0:100 ratio yield the best water absorption, likely due to purun’s hygrscopis.. Conversely, the 100:0 ratio produced the best internal bonding, attributed to meranti’s fiber structure and particle surface supporting adhesive bonding. The findings suggest that particleboard quality is more influenced by raw material–adhesive interactions and process variables, such as adhesive type and content, than by raw material composition variation